Embryonic survival and variation in embryonic development on day 11 of gestation - R M Blair; C M Coughlin; J Ernest Minton; Duane L Davis (Kansas Agricultural Experiment Station Research Reports, 1993)
The primary objective of this study was to determine if embryo survival in gilts and primiparous sows was related to variations in the periovulatory profiles of estradiol- 17Î², progesterone, and luteinizing hormone. A secondary objective was to compare embryo development and certain endocrine characteristics in gilts and primiparous sows. Sows (n=6) and gilts (n=6) were catheterized in the jugular vein on the day after weaning and day 14 of the estrous cycle, respectively. Additional females (1 gilt and 7 sows) were examined for characteristics of embryonic development, but blood samples were not collected. Embryo size and volume on day 11.5 to 11.75 of gestation were recorded. Embryo recovery was 71.4% based on the number of corpora lutea. Minimal differences were observed between sows and gilts for endocrine and embryo data. However, endocrine differences were noted for pigs with high embryo survival (>71% recovery) compared to those with low survival. Peak estradiol-17Î² occurred closer to the onset of estrus in pigs with high embryo survival than in pigs with low embryo survival, and peak LH occurred later after the onset of estrus for pigs with high embryo survival. Also, pigs with high embryo survival tended to have less variation in embryonic development than those with low embryo survival. These data suggest that increased embryo survival and decreased diversity in development might be associated with a closer synchrony between the onset of estrus and peak concentration of estradiol-17Î².; Swine Day, Manhattan, KS, November 18,1993
Keywords: Swine day; 1993; Kansas Agricultural Experiment Station contribution; no. 94-194-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 695; Swine; Pig; Embryo survival; Hormone